A mesoporous silica nanoparticle technology applied in dilute nutrient solution accelerated establishment of zoysiagrass. Issue 1 (14th February 2020) - Adams, Curtis B.; Erickson, John E.; Bunderson, Landon
Abstract: Use of nanoparticles in agriculture is anticipated to have beneficial outcomes, including the potential for improving nutrient delivery. Mesoporous silica nanoparticles (MSNPs) are hydrophilic porous materials with high surface area and charge and have been shown to be taken up and mobilized by plants. Untreated MSNPs have interacted with plant nutrition in controlled studies, but little research has been conducted in the field. In this study, we tested the impact of a commercially available MSNP technology on establishment of two turfgrasses from sprigs in North Central Florida. Treatments included combinations of MSNPs (–NP, with no nanoparticles; +NP, with nanoparticles), which were foliarly applied in dilute nutrient solution, and two rates of background fertility (high and low fertility), which were applied by granular fertilizer. All treatments were applied weekly. The MSNPs were effective in enhancing the rate of establishment in zoysiagrass ( Zoysia japonica Steud.) in combination with both high and low fertility. For the low fertility +NP treatment, this substantially improved nutrient‐use efficiency, as establishment was reduced by just 7.6% compared to the high fertility –NP treatment with 75% less fertilizer. No impact was observed on bermudagrass ( Cynodon dactylon (L.) Pers. × C. Transvaalensis Burtt‐Davy). Tissue nutrient concentrations indicated the nutrients most likely limiting growth were K, Mg, Ca, Zn, and Mn. The results suggest MSNPs provided more effective delivery of one or more limiting nutrients to zoysiagrass than nutrients from other sources, enhancing the rate of growth. The MSNPs offer the potential to establish turfgrasses with lower fertilizer inputs.